Civil szervezetek menedzsmentje - feladatvégrehajtás és státuszvizsgálatok - Pierog, Anita (Közép-Európai Közlemények, 2016)
Driving my research I focus on managerial issues of civil organizations. In my study I describe the result of my research in Hajdú-Bihar County. The primary objectiv of my research is to examine and explore the specialties of the managerial tasks and operation. The result concern to the organizational tasks and status surveys. Quantitative data from an empirical analysis is used for the research. The basis of this sample was the County Court of Justice’s website. The organization of the executive functions are considered the most important managers of the organizations. For the total sample stated the most important tasks of the organization are coordination, ensuring financial conditions, followed by provision of personnel. The status serveys examined of the evaluation of effectiveness. I define the positions inside the civil organizations as legal and behavioral relationships. Volunteers, employees and members are defined as independent positions within the organization. Overall status for all of the organization’s effectiveness and reputation of the most important.